Negotiation Processes: Tactics of Preparing a Successful Negotiation - Alireza Parvaneh; Vahid Akbari (International Journal of Innovation in Marketing Elements)
Negotiation is a fast-paced activity. That is, the negotiation process is evaluated and changed throughout the process, from beginning to end. Before taking any action or retaliating, both sides consider their own interests and aims in order to analyze their own and the other's positions. These judgments and estimations are frequently susceptible to change during the negotiation process. The fresh information that comes in must be categorized and assessed. The dialogue's complexity and difficulty stems from its dynamic and variable nature. If each negotiation has three stages: preparation, advancement and leadership, negotiation, and conclusion, the stage of preparing for the negotiation in advance to accomplish the desired result in a successful negotiation will be very significant and effective. Therefore, in this article, some hints are given as to how to prepare for a successful negotiation by using strategies and tactics.